Bureaucracy Reform in Improving the Quality of Licensing Services - Manbait, Jasinta Juwita; Sayrani, Laurensius Petrus; Libing, Zet Sony (Devotion : Journal of Research and Community Service, 2022)
This study aims to describe the implementation of Bureaucratic Reform and the Quality of Licensing Services at the Investment and One Stop Service Office of East Nusa Tenggara Province. This study uses a qualitative descriptive approach with data analysis techniques using an interactive model developed by Miles and Huberman. This research was conducted at the Investment Office and the One Stop Service Office of East Nusa Tenggara Province with a number of 20 informants consisting of employees and permit applicants as users of licensing services. The sources of data in this study are primary data and secondary data with data collection techniques through interviews, document studies, and observations with validation of research results using triangulation techniques. The results of the study indicate that from the aspect of structuring Human Resources, bureaucratic reform has not been carried out optimally, but from the aspect of structuring management, institutional structuring and accountability, bureaucratic reform has been carried out despite budget constraints. Meanwhile, the quality of licensing in terms of tangible, reliability, responsiveness, assurance, and empathy, has mostly met the expectations of service users despite budget constraints in optimally utilizing technology. Overall, the bureaucratic reforms implemented can improve the quality of licensing services at the Investment and One Stop Service Office of East Nusa Tenggara Province.